Brain handedness associations depend on how and when handedness is measured - Link Tejavibulya; Corey Horien; Carolyn Fredricks; Bronte Ficek-Tani; Margaret L. Westwater; Dustin Scheinost (Scientific Reports)
Abstract Hand preference is ubiquitous, intuitive, and often simplified to right- or left-handed. Accordingly, differences between right- and left-handed individuals in the brain have been established. Nevertheless, considering handedness as a binarized construct fails to capture the variability of brain-handedness associations across different domains or activities. Further, hand-use changes across generations (e.g., letter writing vs. texting) such that individuals of different ages live in different environments. As a result, brain-handedness associations may depend on how and when handedness is measured. We used two large datasets, the Human Connectome Project-Development (HCP-D; n = 465; age = 5–21 years) and Human Connectome Project-Aging (HCP-A; n = 368; age = 36–100 years), to investigate generational differences in brain-handedness associations. Nine items from the Edinburgh Handedness Inventory were associated with resting-state functional connectomes. We show that brain-handedness associations differed across the two cohorts. Moreover, these differences depended on the way handedness was measured. Given that brain-handedness associations differ across handedness measures and datasets, we caution against a one-size-fits-all approach to neuroimaging studies of this complex trait.